2020
DOI: 10.1590/1678-4324-2020200094
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immune Responses and Histopathological Effects against Gamma Irradiated Avian Influenza (Sub type H9N2) Vaccine on Broiler Chicken

Abstract: Vaccination is a good strategy for the prevention of avian influenza virus. In this research Gamma Irradiated Avian Influenza (Sub type H9N2) Vaccine (GAIV) was prepared by 30 kGy irradiation and used for vaccination of broiler chickens. The purpose was a comparison of immune responses in the two routes of administration for the GAIV vaccine; intranasal and subcutaneously, use of Montanide ISA70 and Trehalose accompanied with irradiated vaccine and compare with formalin vaccine. The Influenza Virus A/Chicken/I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In the current investigation, H9N2 AI challenge caused histopathological alterations in several organs; also, vaccination against the H9N2 virus induced moderate histological abnormalities in various organs. Our findings were consistent with the histopathology findings observed by Javan et al (2020) in broiler chickens exposed to gamma irradiated H9N2 AI vaccination. As a result, combining an immune modulator with the vaccine would result in a reduction in vaccine side effects.…”
Section: Discussionsupporting
confidence: 92%
“…In the current investigation, H9N2 AI challenge caused histopathological alterations in several organs; also, vaccination against the H9N2 virus induced moderate histological abnormalities in various organs. Our findings were consistent with the histopathology findings observed by Javan et al (2020) in broiler chickens exposed to gamma irradiated H9N2 AI vaccination. As a result, combining an immune modulator with the vaccine would result in a reduction in vaccine side effects.…”
Section: Discussionsupporting
confidence: 92%
“…The result of the antibody level for the trehalose irradiated vaccine was lower than that for the irradiated vaccine without trehalose. The immune efficiency of the trehalose irradiated vaccine results did not agree with results obtained for the bacteria trehalose vaccine [ 28 ] and the virus trehalose vaccine [ 7 ]. However, Vanaporn and Titball [ 28 ] suggested that the role of trehalose protection depends on the type of bacterial cell and high levels of accumulated trehalose delay the bacteria germination of spores.…”
Section: Discussionmentioning
confidence: 65%
“…It is produced by many invertebrates, a wide variety of plants and algae, bacteria, yeasts, and fungi [ 24 - 27 ]. Trehalose is widely used as a protein stabilizer and cryoprotectant by the food and drug industry [ 7 , 27 , 28 ]. The result of the antibody level for the trehalose irradiated vaccine was lower than that for the irradiated vaccine without trehalose.…”
Section: Discussionmentioning
confidence: 99%
“…The D 10 value (dose of gamma radiation, which can decrease 1 logarithmic cycle of virus population) and optimum dose of gamma rays for virus inactivation were determined according to the dose/response curve. Finally, 2 vials of bivalent polioviruses that include 50 mL of the poliovirus, one of them plus 20% trehalose (1 M) (a disaccharide of glucose, as a protein protectant) and another without trehalose, under frozen conditions were irradiated by the optimized dose of gamma ray and used for safety test on cell culture (during 4 blind cultures) to confirm complete virus inactivation [7].…”
Section: Methodsmentioning
confidence: 99%